Evaluasi Administrasi Pelaksanaan Pemilu Serentak 2019 Terhadap Nilai-Nilai Pancasila - Lita Tyesta ALW (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2019)
Abstract The aim of this paper is to find out the administrative evaluation of the implementation of simultaneous elections in 2019 on the actualization of the values of Pancasila. Writing is an ingredient in the framework of participation in Focus Groups Discussion with the theme